1997
DOI: 10.1111/j.1365-2125.1997.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

The haemodynamic effects of subcutaneous sumatriptan, a 5HT1‐receptor agonist

Abstract: Aims Previous in vivo studies with sumatriptan, a 5HT 1 -receptor agonist, have demonstrated vasopressor responses in the pulmonary and systemic arterial circulation. Pulmonary artery wedge pressure (PAWP) also increases after sumatriptan injection, raising the possibility of an additional venoconstrictive action or a negative inotropic effect. The mechanism for the rise in PAWP was investigated in the study. Methods Ten patients undergoing diagnostic coronary arteriography underwent haemodynamic monitoring. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…In control lungs, 5-HT evoked only a moderate vascular pressor response, which is in line with previous studies [21]. Acute vasoconstriction to 5-HT was mediated by the 5-HT1B receptor in human pulmonary arteries ex vivo [37] and in vivo [38], whereas in normal rat pulmonary arteries, these responses were mediated predominantly by the 5-HT2A receptor [39]. In ex vivo perfused lungs of allergen-sensitised and -challenged mice, as well as control mice, the 5-HT-evoked Ppa responses were blocked by the 5-HT2A receptor antagonist ketanserin, whereas 5-HT1B receptor antagonism by GR127935 did not diminish vasoconstriction.…”
Section: Discussionsupporting
confidence: 77%
“…In control lungs, 5-HT evoked only a moderate vascular pressor response, which is in line with previous studies [21]. Acute vasoconstriction to 5-HT was mediated by the 5-HT1B receptor in human pulmonary arteries ex vivo [37] and in vivo [38], whereas in normal rat pulmonary arteries, these responses were mediated predominantly by the 5-HT2A receptor [39]. In ex vivo perfused lungs of allergen-sensitised and -challenged mice, as well as control mice, the 5-HT-evoked Ppa responses were blocked by the 5-HT2A receptor antagonist ketanserin, whereas 5-HT1B receptor antagonism by GR127935 did not diminish vasoconstriction.…”
Section: Discussionsupporting
confidence: 77%
“…19,30 An increase in aortic blood pressure has been observed previously in patients undergoing diagnostic coronary angiography, by use of invasive blood pressure monitoring. 4,5,7,31,32 However, in these studies no comparisons were made with simultaneously measured brachial blood pressure. A novel finding of our study is that the central increase in SBP was more pronounced than the peripheral increase in SBP.…”
Section: Discussionmentioning
confidence: 99%
“…Hood et al demonstrated significant increase in left ventricular end diastolic and pulmonary artery wedge pressures following subcutaneous sumatriptan [8]. Altered atrial filling resulting from these haemodynamic changes could be responsible for initiating AF [9].…”
Section: Review Of Literature and Discussionmentioning
confidence: 97%